Resonance microwave compressor in the transmitter of a nonlinear pulse radar; Radiotekhnika; № 4 - Novikov S. A. Sergey Avtonomovich (2001, 2001)
The breadboard characteristics and operation investigation results are presented for a resonance microwave compressor which increases power and reduces duration of pulses exciting its accumulating resonance volume. This source of output microwave pulses with power 240 kW, duration 10 ns, frequency repetition 100 Hz and carrier frequency 934 MHz was used in the transmitter of a nonlinear radar breadboard. The receiver frequency bandwidth was not less than 120 MHz.